Agency and empowerment in consumption in relation to a patriarchal bargain: The case of Nigerian immigrant women in the UK. Issue 9 (12th September 2016) - Lindridge, Andrew; Peñaloza, Lisa; Worlu, Onipreye
Abstract : Purpose: This research aims to explore how female immigrants use consumption to challenge and support their husband's position within the context of their patriarchal bargain. Design/methodology/approach: The sample group ( n = 20) consisted of ten first-generation Nigerian immigrant married couples living in Britain, who were interviewed together, with the married female then re-interviewed separately. Findings: This paper demonstrates how women transition from being a wife in a consanguine family in Nigeria, which they describe as patriarchal, to becoming one within a nuclear family in the UK, a society to which they attribute gender equality. Nigerian immigrant women alter their ways of thinking and consuming, with implications to their agency and empowerment. In particular, consumption choices demonstrated the limits of these women's willingness to challenge their patriarchal bargain and instead often colluded with their husbands to maintain his position as the head of the family. Practical implications: Immigrant women should not be seen as passive receptors of their male partner's wishes or demands, but instead active participators in purchasing and consumption decisions. Although marketing encourages direct targeting of customers, this approach raises a number of ethical issues for female African immigrants. Originality/value: Previous research on the consumption behaviour of immigrants is limited in scope and tends to focus on male immigrants, with female immigrants either invisible or stereotyped. Compounding this problem are disciplinary, geographical and linguistic barriers that hinder social scientists' research into the consumption of female migration. This paper works to address these omissions.